PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN GOOGLE SITES UNTUK MATERI GOTONG ROYONG DILINGKUNGAN SEKITARKU MUATAN PENDIDIKAN PANCASILA DI GUGUS VII SEKOLAH DASAR - Ardiawan, I Ketut Ngurah (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
: This research aims to produce interactive learning media in the form of learning poetry media assisted by Google Sites for material on Mutual Cooperation in the Environment Around Me in the class V Pancasila Education subject in Gugus VII Buleleng District that is valid and practical. The method used in this research is the Research and Development method with the ADDIE (Analyze Design, Develop, Implement and Evaluate) development design. The ADDIE model is used until the Develop stage. This research also uses a questionnaire to obtain data about the level of validity of learning media. This questionnaire was completed by three experts consisting of material experts, language experts and media experts. The research results show that the learning poetry media assisted by Google Sites obtained a score of 0.90 out of the total scores given by the three experts. The practicality test also used a questionnaire with respondents consisting of 3 fifth grade teachers. The practicality results obtained an average of 0.92 with very high validity. From these results, research and development on learning poetry media assisted by Google Sites for Mutual Cooperation in the Environment Around Me material in Pancasila Education subjects was categorized as very valid, practical and suitable for use.